Fatal and Nonfatal Events Within 14 days After Early, Intensive Mobilization Poststroke - Bernhardt, J.; Borschmann, K.; Collier, J.M.; Thrift, A.G.; Langhorne, P.; Middleton, S.; Lindley, R.I.; Dewey, H.M.; Bath, P.; Said, C.M.; Churilov, L.; Ellery, F.; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Objective This tertiary analysis from A Very Early Rehabilitation Trial (AVERT) examined fatal and nonfatal serious adverse events (SAEs) at 14 days. Method AVERT was a prospective, parallel group, assessor blinded, randomized international clinical trial comparing mobility training commenced <24 hours poststroke, termed very early mobilization (VEM), to usual care (UC). Primary outcome was assessed at 3 months. Patients with ischemic or hemorrhagic stroke within 24 hours of onset were included. Treatment with thrombolytics was allowed. Patients with severe premorbid disability or comorbidities were excluded. Interventions continued for 14 days or hospital discharge if less. The primary early safety outcome was fatal SAEs within 14 days. Secondary outcomes were nonfatal SAEs classified as neurologic, immobility-related, and other. Mortality influences were assessed using binary logistic regression adjusted for baseline stroke severity (NIH Stroke Scale [NIHSS] score) and age. Results A total of 2,104 participants were randomized to VEM (n = 1,054) or UC (n = 1,050) with a median age of 72 years (interquartile range [IQR] 63–80) and NIHSS 7 (IQR 4–12). By 14 days, 48 had died in VEM, 32 in UC, age and stroke severity adjusted odds ratio of 1.76 (95% confidence interval 1.06–2.92, p = 0.029). Stroke progression was more common in VEM. Exploratory subgroup analyses showed higher odds of death in intracerebral hemorrhage and >80 years subgroups, but there was no significant treatment by subgroup interaction. No difference in nonfatal SAEs was found. Conclusion While the overall case fatality at 14 days poststroke was only 3.8%, mortality adjusted for age and stroke severity was increased with high dose and intensive training compared to usual care. Stroke progression was more common in VEM.